On one classification of transcendental numbers - Sprindzuk, V. G. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Г. Спринджук. Об одной классификации транцендентных чиселV. Sprindžiuk. Apie vieną transcendentinių skaičių klasifikaciją